Warunki rozwoju pracowniczych programów emerytalnych - Pieńkowska-Kamieniecka, Sylwia (The Conditions for the Development of Occupational Pension Schemes, 2008)
Occupational pension schemes with individual retirement accounts create the third pillar of the Polish new retirement system. The main reason why employers decided on the creation of occupational pension schemes in their enterprises was the necessity to transform the existing form of group pension plans if they wanted to keep relief in paying contributions for national social insurance fund. The main conclusion is that despite the satisfaction with the way in which the schemes work, the third pillar does not prosper well. The main reason is that in Poland exists the TEE model, called pre-paid regime, while the EET system would be better. Besides, the society needs more promotional and educational campaigns to encourage creating and participating in occupational pension schemes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 344-351